2010
DOI: 10.2971/jeos.2010.10003
|View full text |Cite
|
Sign up to set email alerts
|

Sub surface damage measurements based on short coherent interferometry

Abstract: During grinding step in manufacturing process of glass lenses it is important to control such parameters as shape and sub-surface damage (SSD) with high accuracy which essentially influences the duration and costs of the subsequent polishing process. Typically used methods suffer from limited resolution and are time consuming. That is why the nondestructive measurement of SSD is a challenge for the metrology of grinded surfaces. In order to detect these damages, the scanning short-coherence interferometer, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…SSD depth can be empirically predicted with the size of abrasive grains during grinding or lapping, for which several researchers arrived at different results [40,[55][56][57][58]. Lambropoulos et al [59] proposed a relationship between the damage depth and the size of abrasive grains, expressed as Eq.…”
Section: Predictive Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SSD depth can be empirically predicted with the size of abrasive grains during grinding or lapping, for which several researchers arrived at different results [40,[55][56][57][58]. Lambropoulos et al [59] proposed a relationship between the damage depth and the size of abrasive grains, expressed as Eq.…”
Section: Predictive Methodsmentioning
confidence: 99%
“…However, the images were blur because of the strong surface scattering, weak subsurface scattering and big tomography interval. Sergeeva et al [57] used the short coherent interferometry to measure the artificial SSD in a glass, and reported that the depth and lateral resolution were 10 μm and 4 μm, respectively. While in a practical situation, cracks show more complex configurations, such as "chevron", "branch" and "fork" [73].…”
Section: (8)mentioning
confidence: 99%
“…Guss et al 112 used OCT to accurately obtain SSD images from fused silicon and measure cracks 300 μm below the surface. Sergeeva et al 113 used OCT to measure the SSDs in optical glass lenses and obtained depth direction and transverse resolutions of 10 and 4 μm, respectively.…”
Section: Nondestructive Detectionmentioning
confidence: 99%
“…They expose SSDs through physical or chemical means, and will cause irreversible damage to the optics. Non-destructive methods based on optical imaging include total internal reflection microscope (TIRM) [11] , confocal laser scanning microscope(CLSM) [12,13] , and optical coherence tomography(OCT) [14] , etc. They illuminate the detection area in different ways, receive the optical signal modulated by SSDs, and will not cause damage.…”
Section: Introductionmentioning
confidence: 99%